Setting Time and Surface Microhardness of Mineral Trioxide Aggregate and 1% and 5% Fluoride-Doped Mineral Trioxide Aggregate Mixed with Water and Gel-like Polymer - Dianat, Omid; Mahdian, Arezoo; Sanagoo, Nazanin; Mozayeni, Mohammad Ali; Eskandarion, Solmaz (Iranian Endodontic Journal, 2019)
Introduction: Mineral trioxide aggregate (MTA) is extensively used in endodontics. However, it has limitations such as long setting time, low compressive strength and poor handling properties. Our study aimed to compare the setting time and surface microhardness of MTA and fluoride-doped MTA (FMTA) using gel-like polymer (GLP) or distilled water (DW) as liquid. Methods and Materials: An MTA-like cement was prepared by mixing Portland cement, bismuth oxide and gypsum (75%, 20% and 5%, respectively). FMTA (1% and 5%) was made by substituting 1% and 5% of MTA powder with fluoride. GLP, composed of methyl cellulose (MC) and propylene glycol (PG), was used as the hydrating liquid and compared with distilled water. Six experimental groups (n=10) were examined for each test. The samples were subjected to Vickers surface microhardness test after 4 and 28 days. Setting time was measured using ANSI/ADA standards. Data was analyzed using two-way and repeated measured ANOVA and the Tukey HSD tests. Results: The MTA-like cement hydrated with GLP showed a significantly reduced setting time (P<0.05); 1% FMTA, mixed with GLP, had the shortest initial and final setting times. The microhardness values of all samples increased at different rates during 28 days (P<0.00001). The microhardness significantly decreased by addition of fluoride to MTA (P<0.001). Conclusions: The results of the present in vitro study suggested that using GLP as the hydrating liquid enhances the setting time with no adverse effect on the surface microhardness. However, adding fluoride can negatively affect the microhardness of MTA. Keywords: Fluoride-oped Mineral Trioxide Aggregate; Microhardness; Mineral Trioxide Aggregate; Setting Time